(untitled) (American Journal of Islam and Society, 2004)
While Ashutosh Varshney’s book, Ethnic Conflict and Civic Life: Hindus and Muslims in India, cannot be judged by its cover, it can be judged by its index. His exhaustive and erudite study of riots in India only includes a paltry three references to the Rashtriya Swayemsevak Sangh (RSS) and Vishwa Hindu Parishad (VHP), two Hindu nationalist organizations that play a central role in such riots. He also fails to mention the Bajrang Dal, the militant Hindu organization responsible for many of the attacks during the violence in Gujarat in 2002. This seems to summarize the problem with his book: It is intriguing yet incomplete. The reason for this omission becomes clear from his central thesis: Riots seldom occur where integrated networks of civic engagement exist; riots are a common feature where interdependency is absent. Varshney, a professor of political science at the University of Michigan, surveys six cities in India: three riot-prone (Hyderabad, Ahmedabad, Aligarh) and three riot-free (Lucknow, Calicut, Surat). His focus on India’s urban centers is not without reason. Only 4% of communal violence-related deaths have occurred in rural areas, where 67% of the Indian population lives. Eight cities (whose total population is only 5% of the country’s total population) account for 45% of deaths in communal violence. Varshney seems overly eager to correct the notion that Hindu-Muslim violence is a pan-Indian experience. His book highlights some important divisions that contribute to interreligious discord. In chapter 5, for example, he notes that Aligarh Muslim University (AMU), once an educational center for both Muslims and Hindus, is now largely a university exclusively attended by Muslims. Such divisions at the higher academic levels lead to inevitable cleavages in society. Varshney concludes that “local patterns of violence underline how important associational ties across communities are for peace in multi-ethnic societies” (p. 11). It is tempting to agree with Varshney. His book suggests the basic premise that if Muslims and Hindus work together, they will not resort to communal violence. One can understand why his ideas have gained support from government officials, apologetic Indian scholars, and ...